Pengaruh pH Dan Suhu Terhadap Stabilitas Antosianin Dari Ekstrak Kulit Ubi Jalar Ungu (Ipomoea Batatas (L.) Lam.) - Sandra tri juli fendri; B A Martinus; Meindika Dwi Haryanti (Universitas Jambi, Fakultas Sains dan Teknologi, Program Studi Kimia, 2017)
The aim of this research is to knowing about the stability of anthocyanin dye against the influence of pH and temperature, and also degradation of color from purple sweet potato’s peel extracts. The process of sweet potato extraction was done by maceration using ethanol 96%. Anthocyanin stability test was performed on the pH, and variation of pH are 1, 3, 5, 7 and 9. While, temperature variation that used are room temperature, 40°C, 60°C, 80°C and 100°C. To know the absorbance value for color degradation of anthocyanin was measured using a UV-Vis spectrophotometer at 528 nm wavelength maximum. The results of analysis data statistic by using (ANOVA) two way advanced to Duncan test (SPSS 17.0) in stability of pH and temperature are showed that samples more stabile at pH 1 than pH 3 and 5 because there are significant value. The result of % color degradation from pH sample 1, 3 and 5 respectively are 1,47% ; 49,63% and 52,32%.